Pengaruh pijat laktasi pada ibu nifas terhadap produksi ASI - Naili Rahmawati; Indra Karana (Holistik Jurnal Kesehatan, 2023)
Background: The factor that influences breastfeeding is the feeling of comfort after giving birth. One way to stimulate the hormone oxytocin and increase comfort is with lactation massage. Profile of exclusive breastfeeding in West Java as many as 349,968 (46.4 percent) infants aged 0-6 months out of 754,438 babies 0-6 months who received exclusive breastfeeding, however Bandung City that have exceeded the national target of about 97.4 percent.Purpose: To determine the effect of lactation massage on breast milk production in Midwives Independent Practice ‘D’ Bandung City.Method: A quasi-experimental research type with a posttest-only design. The sampling technique used purposive sampling with a number of participants as many as 30 people. Data were collected using a checklist and processed by statistical tests, namely the independent sample T-test.Results: The results show that the bivariate analysis test showed that significant relationship between the effect of lactation massage on postpartum mothers on milk production with the p-value was 0,000 < 0.05.Conclusion: There is a significant effect of lactation massage on milk production in postpartum mothers.Keywords: Post-Partum; Lactation; Massage; Breast Milk Production.Pendahuluan: Faktor yang mempengaruhi pemberian ASI adalah rasa nyaman setelah melahirkan. Salah satu cara untuk merangsang hormon oksitosin dan meningkatkan rasa nyaman adalah dengan pijat laktasi. Profil Pemberian ASI eksklusif di Jawa Barat sebanyak 349.968 (46,4 persen) bayi umur 0-6 bulan dari 754.438 jumlah bayi 0-6 bulan yang mendapatkan ASI eksklusif, walaupun demikian Kota Bandung telah melampaui target nasional, yaitu 97,4 persen.Tujuan: Mengetahui pengaruh pijat laktasi terhadap produksi ASI di Praktik Mandiri Bidan ‘D’ Kota Bandung.Metode: Penelitian ini menggunakan jenis penelitian quasi eksperimental dengan desain posttest only. Tehnik pengambilan sampel menggunakan purposive sampling dengan jumlah partisipan sebanyak 30 orang. Data dikumpulkan dengan lembar cek list dan diolah dengan uji statistic yakni uji independen sample T-test.Hasil: Penelitian menunjukkan bahwa hasil uji analisis bivariat, didapatkan hubungan yang signifikan pengaruh pijat laktasi pada ibu nifas terhadap produksi ASI dengan nilai p-value yaitu 0,000 < 0,05.Simpulan: Terdapat pengaruh pijat laktasi terhadap produksi ASI pada ibu nifas secara signifikan.